A method for connecting AlON transparent ceramics and alumina ceramics with green and low-cost glass

By using lead-free glass solder as the intermediate layer, the effective connection of AlON transparent ceramics and Al2O3 ceramics is achieved at a lower temperature, which solves the problem of high soldering temperature in the existing technology and achieves a joint with high strength and airtightness. .

CN117362065BActive Publication Date: 2025-01-21HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311555805.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-21
Publication Date
2025-01-21
Estimated Expiration
2043-11-21

AI Technical Summary

Technical Problem

The brazing temperature of existing AlON transparent ceramics and Al2O3 ceramics is relatively high, making it difficult to achieve effective connection at lower temperatures.

Method used

Lead-free glass solder composed of Bi2O3, B2O3 and CaO is used as the intermediate layer. The glass powder obtained by firing and ball milling at 1000℃~1100℃ is pressed into a green body and then brazed at 700℃~800℃. , to realize the connection between AlON transparent ceramics and Al2O3 ceramics.

Benefits of technology

The low-temperature pressure-free connection of AlON transparent ceramics and Al2O3 ceramics is realized. The glass filling in the weld is uniform, and there are a small number of pores but does not affect the air tightness of the joint. The maximum shear strength at room temperature is about 31MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117362065B_ABST
    Figure CN117362065B_ABST
Patent Text Reader

Abstract

A method for connecting AlON transparent ceramics and alumina ceramics with green and low-cost glass, and relates to a method for connecting AlON transparent ceramics and alumina ceramics. The present invention is to solve the technical problem that the existing AlON transparent ceramics and Al2O3 ceramics have high brazing temperatures. The present invention uses Bi2O3‑B2O3‑CaO glass as an intermediate layer for connecting dissimilar ceramics, and adopts direct brazing under air to achieve the connection of AlON and Al2O3 dissimilar ceramics, wherein the lead-free glass solder has good fluidity and excellent wetting performance with the parent materials on both sides, and at the same time, the connection layer has few defects and high reliability. The thermal expansion coefficient of the low-temperature lead-free glass solder provided by the present invention is very close to that of AlON ceramics and Al2O3 ceramics. The maximum shear strength of the obtained joint at room temperature is about 31MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for connecting AlON transparent ceramics and alumina ceramics. Background Art

[0002] Aluminum oxynitride (AlON) ceramics are isotropic single-phase transparent ceramics with a hardness four times that of quartz glass and 85% that of sapphire, and can withstand high temperatures of 1200°C. In addition, due to its excellent mechanical and optical properties, transparent AlON ceramics can be used in infrared windows, transparent armor, and scratch-resistant windows. In recent years, research on AlON ceramics has mostly focused on the preparation of small-sized laboratory samples to study their optical and mechanical properties. In fact, it is not easy to directly manufacture large-sized AlON components using existing equipment and technology. Therefore, from the perspective of practical engineering applications, it is of great significance to develop a connection technology between transparent AlON ceramics and dissimilar materials.

[0003] At present, the research on the connection of AlON transparent ceramics has attracted the attention of more and more scholars. Regarding the connection of AlON itself, Wang Guang et al. successfully achieved pressureless connection by using a powder intermediate layer of the parent material at 1880℃ for 80 minutes (Scripta Materialia 171(2019)118–121; A method for connecting AlON ceramics using AlON powder as a raw material, invention patent, 201910195181.0). In addition, Lu-Al-Si-ON oxynitride glass and β-SiAlON / Y-Si-Al-ON glass ceramics can also be used as connecting materials to achieve the connection of AlON ceramics (Ceramics International45(2)(2019)2591-2595; Journal of Non-Crystalline Solids 503(2019)389-396). For the connection between AlON transparent ceramics and dissimilar materials, Li Chun et al. used active brazing alloy AgCuTi to braze AlON with Ti6Al4V and Ti2AlNb under vacuum conditions (Materials Science and Engineering: A 793 (19) 2020139859; Materials Science and Engineering: A846 (27) 2022 143277.). The active brazing alloy can achieve connection through chemical reaction with AlON transparent ceramics. Al2O3 ceramics have excellent mechanical properties and low cost, and have been widely used in aerospace, microelectronics, automobile transportation and other fields. They can be used as supporting structures to connect with AlON transparent ceramics, combining the performance advantages of both ceramics to achieve engineering applications. For the connection research between the two, (A method for connecting AlON / Al2O3 ceramics, invention patent: 202210851369.8) reported that the use of AlON powder with Y2O3 and Al2O3 sintering aids to achieve the connection between AlON ceramics and Al2O3 ceramics at 1860-1900℃. However, there is no research on brazing AlON transparent ceramics and Al2O3 ceramics at lower temperatures. The connection between AlON ceramics and Al2O3 ceramics is a connection problem between heterogeneous ceramic materials. The intermediate layer material needs to have good compatibility with both AlON ceramics and Al2O3 ceramics. Glass brazing filler metal is a connection material with good wetting on the surface of oxide ceramics and excellent connection performance. It is expected to achieve low-temperature pressureless connection between AlON ceramics and Al2O3 ceramics. Summary of the invention

[0004] The present invention aims to solve the technical problem of high brazing temperature of existing AlON transparent ceramics and Al2O3 ceramics, and provide a method for connecting AlON transparent ceramics and alumina ceramics with green and low-cost glass.

[0005] The method for connecting AlON transparent ceramic and alumina ceramic with green low-cost glass of the present invention is carried out according to the following steps:

[0006] Step 1: Evenly mix Bi2O3 powder, B2O3 powder and CaO powder to obtain lead-free glass solder, then fill it into a crucible, keep it in a muffle furnace at 1000℃~1100℃ for 2h~2.5h to obtain liquid glass, then quickly pour the liquid glass into deionized water to obtain glass pieces, and then obtain glass powder through ball milling process, the average size of the glass powder is ≤5 microns;

[0007] The lead-free glass solder is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 80% to 85%, the mass fraction of B2O3 is 10% to 20%, and the balance is CaO;

[0008] Step 2: grinding, ultrasonic cleaning and drying the to-be-welded parts of the base material AlON transparent ceramic and the Al2O3 ceramic in sequence;

[0009] Step 3: Press the glass powder prepared in step 1 into a green body, and press the green body into a thickness of 400 microns to 600 microns; place the glass solder green body between two ceramic matrix materials as an intermediate layer, and the two ceramic matrix materials are respectively located at the upper layer and the lower layer, and put them into a muffle furnace;

[0010] Step 4: Heat from room temperature to brazing temperature at a heating rate of 10°C / min to 20°C / min and keep warm for 5min to 30min, then cool to 300°C to 310°C at a rate of 5°C / min to 10°C / min, and then cool naturally to room temperature with the furnace;

[0011] The brazing temperature is 700° C. to 800° C. in an air environment.

[0012] Compared with the prior art, the present invention provides a low-temperature lead-free glass solder and realizes the connection between AlON ceramic and Al2O3 ceramic under pressureless conditions. The beneficial effects are:

[0013] The low-temperature lead-free glass solder provided by the present invention is used for the method for connecting AlON transparent ceramics and Al2O3 ceramics. Bi2O3-B2O3-CaO glass is used as the intermediate layer for connecting dissimilar ceramics, and direct brazing under air is used to achieve the connection of AlON and Al2O3 dissimilar ceramics. The lead-free glass solder has good fluidity and excellent wetting performance with the parent materials on both sides. At the same time, the connection layer has few defects and high reliability. The thermal expansion coefficient of the low-temperature lead-free glass solder provided by the present invention is 8.2×10 -6 / K, compared with AlON ceramics (7.8×10 -6 / K) and Al2O3 ceramics (6.5~7.5×10 -6 / K) is very close. During the connection process, the glass interacts with the two base materials. After the surfaces of the AlON and Al2O3 ceramic base materials come into contact with the liquid glass, they both dissolve a small amount into the liquid glass, especially the melting at the grain boundaries of the ceramic base materials is more obvious, which is beneficial to the interface bonding after cooling, making the connection interface non-straight, playing a mechanical interlocking role, and is beneficial to the improvement of the joint performance. The glass is evenly filled in the weld, and there are a small amount of pores, which are closed-cell structures and do not affect the airtightness of the joint. The maximum room temperature shear strength of the joint obtained by keeping warm at 750°C for 10 minutes in step 4 is about 31MPa.

[0014] Therefore, the present invention adopts green and low-cost glass solder as the intermediate layer for connecting AlON transparent ceramics and Al2O3 ceramics, which can achieve good wetting and interface bonding of the parent materials, thereby realizing the forming and manufacturing of heterogeneous ceramic structural parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The thermal expansion curve of the glass solder prepared in step 1 of Example 2;

[0016] Figure 2 This is a microstructure diagram of the joint obtained in Example 2;

[0017] Figure 3 This is the interface microstructure diagram of the joint obtained in Example 2;

[0018] Figure 4 This is the energy spectrum of element composition in the joint brazing seam obtained in Example 2. DETAILED DESCRIPTION

[0019] Specific implementation method 1: This implementation method is a method for connecting AlON transparent ceramics and Al2O3 ceramics with green low-cost glass, which is specifically carried out in the following steps:

[0020] Step 1: Evenly mix Bi2O3 powder, B2O3 powder and CaO powder to obtain lead-free glass solder, then fill it into a crucible, keep it in a muffle furnace at 1000℃~1100℃ for 2h~2.5h to obtain liquid glass, then quickly pour the liquid glass into deionized water to obtain glass pieces, and then obtain glass powder by ball milling, the average size of the glass powder is ≤5 microns;

[0021] The lead-free glass solder is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 80% to 85%, the mass fraction of B2O3 is 10% to 20%, and the balance is CaO;

[0022] Step 2: grinding, ultrasonic cleaning and drying the to-be-welded parts of the base material AlON transparent ceramic and the Al2O3 ceramic in sequence;

[0023] Step 3: Press the glass powder prepared in step 1 into a green body, and press the green body into a thickness of 400 microns to 600 microns; place the glass solder green body between two ceramic matrix materials as an intermediate layer, and the two ceramic matrix materials are respectively located at the upper layer and the lower layer, and put them into a muffle furnace;

[0024] Step 4: Heat from room temperature to brazing temperature at a heating rate of 10°C / min to 20°C / min and keep warm for 5min to 30min, then cool to 300°C to 310°C at a rate of 5°C / min to 10°C / min, and then cool naturally to room temperature with the furnace;

[0025] The brazing temperature is 700° C. to 800° C. in an air environment.

[0026] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the rotation speed of the ball mill in step 1 is 300 rpm to 400 rpm. The rest is the same as the specific implementation method 1.

[0027] Specific implementation method 3: This implementation method is different from specific implementation method 2 in that the ball milling time in step 1 is 24 hours. The rest is the same as specific implementation method 2.

[0028] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the lead-free glass solder described in step 1 is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 82%, the mass fraction of B2O3 is 15.5%, and the balance is CaO. The rest is the same as specific embodiments 1 to 3.

[0029] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that: in step 1, the temperature is kept at 1000° C. for 2 hours in the muffle furnace. The rest is the same as specific embodiment 4.

[0030] Specific implementation method 6: This implementation method is different from specific implementation method 1 in that the lead-free glass solder described in step 1 is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 85%, the mass fraction of B2O3 is 12%, and the balance is CaO. The rest is the same as specific implementation method 1.

[0031] Specific embodiment 7: This embodiment differs from specific embodiment 6 in that in step 4, the temperature is raised from room temperature to the brazing temperature at a heating rate of 10°C / min and kept at this temperature for 10 minutes. The rest is the same as specific embodiment 6.

[0032] Specific implementation example eight: This implementation example is different from specific implementation example seven in that: in step four, the temperature is lowered to 300° C. at a rate of 5° C. / min. The rest is the same as specific implementation example seven.

[0033] Specific embodiment 9: This embodiment is different from specific embodiment 6 in that the brazing temperature in step 4 is 750° C. and is performed in an air environment. The rest is the same as specific embodiment 6.

[0034] Specific embodiment 10: This embodiment is different from specific embodiment 6 in that the brazing temperature in step 4 is 700° C. and is performed in an air environment. The rest is the same as specific embodiment 6.

[0035] The present invention is verified by the following 7 embodiments:

[0036] The following embodiment is a method for connecting AlON transparent ceramic and Al2O3 ceramic with green low-cost glass, which is specifically carried out according to the following steps:

[0037] Step 1: Evenly mix Bi2O3 powder, B2O3 powder and CaO powder to obtain lead-free glass solder, then fill it into a crucible, keep it warm in a muffle furnace to obtain liquid glass, then quickly pour the liquid glass into deionized water to obtain glass pieces, and then obtain glass powder by ball milling, the average size of the glass powder is ≤5 microns; the ball milling speed is 400 rpm, and the ball milling time is 24 hours;

[0038] The lead-free glass solder described in step 1 is composed of three oxides: Bi2O3, B2O3 and CaO. The specific proportions of the three are shown in Table 1.

[0039] The holding temperature and holding time of the muffle furnace in step 1 are shown in Table 1;

[0040] Step 2: grinding, ultrasonic cleaning and drying the to-be-welded parts of the base material AlON transparent ceramic and the Al2O3 ceramic in sequence;

[0041] Step 3: Press the glass powder prepared in step 1 into a green body to a thickness of 500 microns; place the glass solder green body between two ceramic matrix materials as an intermediate layer, the two ceramic matrix materials are located at the upper layer and the lower layer respectively, and put them into a muffle furnace;

[0042] Step 4: In an air environment, heat the sample from room temperature to the brazing temperature at a heating rate of 10°C / min and keep the temperature, then cool the sample to 300°C at a rate of 5°C / min, and then cool the sample naturally to room temperature.

[0043] The brazing temperature and holding time are shown in Table 1. The room temperature shear strength of the joint is shown in Table 1.

[0044] Table 1

[0045]

[0046] Figure 1 The thermal expansion curve of the glass solder (glass powder) prepared in step 1 of Example 2 shows that the thermal expansion coefficient of the glass solder is 8.2×10 -6 / K.

[0047] Figure 2 This is the microstructure diagram of the joint obtained in Example 2, 1 is Al2O3 ceramic, 2 is the solder intermediate layer, 3 is AlON transparent ceramic. It can be seen from the figure that the brazing seam width is about 30 microns, there are no defects such as cracks and unwelded parts, and there is a small amount of closed-cell structure.

[0048] Figure 3 This is the interface microstructure diagram of the joint obtained in Example 2, 1 is Al2O3 ceramic, 2 is the solder intermediate layer, and 3 is AlON transparent ceramic. It can be seen from the figure that the glass interacts with the two base materials. After the surfaces of the AlON ceramic base materials and the Al2O3 ceramic base materials come into contact with the liquid glass, they both dissolve slightly into the liquid glass. The melting at the grain boundary of the ceramic base material is more obvious. A small amount of AlON grains peel off and remain at the interface, making the connection interface non-straight, playing a mechanical interlocking role, which is beneficial to the improvement of the joint performance.

[0049] Figure 4 : This is the energy spectrum of element composition in the joint brazing seam obtained in Example 2. Table 2 is the corresponding point analysis data of each element content. From the composition, it is determined that there is Al element in the formed glass brazing seam, which means that the base material has dissolved into the brazing filler metal to a certain extent, and the glass and the base material have good chemical compatibility.

[0050] Table 2

[0051] element Atomic Percent O 73.88 Al 5.52 Ca 2.60 Bi 17.99 Total 100.00

Claims

1. A method for connecting AlON transparent ceramics and Al2O3 ceramics with green low-cost glass, characterized in that The method of green low-cost glass bonding AlON transparent ceramic and Al2O3 ceramic is carried out in the following steps: Step 1: Evenly mix Bi2O3 powder, B2O3 powder and CaO powder to obtain lead-free glass solder, then fill it into a crucible, keep it in a muffle furnace at 1000℃~1100℃ for 2h~2.5h to obtain liquid glass, then quickly pour the liquid glass into deionized water to obtain glass pieces, and then obtain glass powder by ball milling, the average size of the glass powder is ≤5 microns; The lead-free glass solder is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 80% to 85%, the mass fraction of B2O3 is 10% to 20%, and the balance is CaO; Step 2: grinding, ultrasonic cleaning and drying the parts to be welded of the base material AlON transparent ceramic and Al2O3 ceramic in sequence; Step 3: Press the glass powder prepared in step 1 into a green body, and press the green body into a thickness of 400 microns to 600 microns; place the glass solder green body between two ceramic matrix materials as an intermediate layer, and the two ceramic matrix materials are respectively located at the upper layer and the lower layer, and put them into a muffle furnace; Step 4: Heat from room temperature to brazing temperature at a heating rate of 10°C / min to 20°C / min and keep warm for 5min to 30min, then cool to 300°C to 310°C at a rate of 5°C / min to 10°C / min, and then cool naturally to room temperature with the furnace; The brazing temperature is 700° C. to 800° C. in an air environment.

2. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that The rotation speed of the ball mill in step 1 is 300 rpm to 400 rpm.

3. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 2, characterized in that The ball milling time in step 1 is 24 h.

4. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that The lead-free glass solder described in step 1 is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 82%, the mass fraction of B2O3 is 15.5%, and the balance is CaO.

5. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that In step 1, the temperature is kept at 1000° C. for 2 h in a muffle furnace.

6. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that The lead-free glass solder described in step 1 is composed of three oxides: Bi2O3, B2O3 and CaO, wherein the mass fraction of Bi2O3 is 85%, the mass fraction of B2O3 is 12%, and the balance is CaO.

7. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that In step 4, the temperature is raised from room temperature to the brazing temperature at a heating rate of 10°C / min and kept at this temperature for 10 minutes.

8. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that In step 4, the temperature is lowered to 300°C at a rate of 5°C / min.

9. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that The brazing temperature described in step 4 is 750° C. in an air environment.

10. The method for connecting AlON transparent ceramic and Al2O3 ceramic by green low-cost glass according to claim 1, characterized in that The brazing temperature described in step 4 is 700° C. in an air environment.

Citation Information

Patent Citations

  • A method for bonding AlON ceramics using AlON powder as a raw material

    CN109721379B

  • Method for connecting AlON / Al2O3 ceramics

    CN115417686A